Rapid decomposition of leaf litter from fast-growing tropical wood jabon (Anthocephalus cadamba Miq.) - Atunnisa Rifa; Mansur Irdika; Rusdiana Omo (E3S Web of Conferences, 2024)
Nutrient releases are considered functional processes related to soil fertility. In fast-growing tree plantation, maintaining the nutrient supply in soil is crucial for sustaining productivity. Jabon (Anthocephalus cadamba Miq.) is one of Indonesia’s native species that belongs to fast-growing species. In fast-growing tree plantation, leaf litter decomposition is considered an essential process of soil fertility. This study was conducted to gain information on the decomposition rate of a 4-year-old jabon plantation. The rate decay constant (k) is 0.09 week-1, and the relative decomposition rate is 0.086 g g-1 week-1. The 50 % (half lifetime) mass loss projection ranged between 53 days. The results suggested that jabon has rapid decomposition rates, implying that jabon has the high prospect for revegetation, particularly in degraded areas.